Body Mapping as a Youth Sexual Health Intervention and Data Collection Tool. (June 2018) - Lys, Candice; Gesink, Dionne; Strike, Carol; Larkin, June
In this article, we describe and evaluate body mapping as (a) an arts-based activity within Fostering Open eXpression Among Youth (FOXY), an educational intervention targeting Northwest Territories (NWT) youth, and (b) a research data collection tool. Data included individual interviews with 41 female participants (aged 13–17 years) who attended FOXY body mapping workshops in six communities in 2013, field notes taken by the researcher during the workshops and interviews, and written reflections from seven FOXY facilitators on the body mapping process (from 2013 to 2016). Thematic analysis explored the utility of body mapping using a developmental evaluation methodology. The results show body mapping is an intervention tool that supports and encourages participant self-reflection, introspection, personal connectedness, and processing difficult emotions. Body mapping is also a data collection catalyst that enables trust and youth voice in research, reduces verbal communication barriers, and facilitates the collection of rich data regarding personal experiences.